Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Salon Kecantikan Glambypuri - Zakaria Zakaria; Atika Nur Zikriyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This research is motivated by the fierce competition in the rapidly growing beauty industry. The purpose of this study is to analyze the effect of Price and Service Quality on Consumer Satisfaction at Glambypuri Beauty Salon. The method used is quantitative. The population in this study was all Glambypuri consumers from August 2025 to August 2025, totaling 500 people. A sample of 83 respondents was obtained using the Slovin formula. Data collection techniques were carried out by distributing questionnaires. Data analysis employed validity and reliability tests, classical assumption tests, regression analysis, coefficient of determination analysis, and hypothesis testing. The findings indicate that both Price and Service Quality play a significant role in shaping Consumer Satisfaction. Each factor individually influences how consumers perceive value and service experience, while their combined effect further strengthens overall satisfaction. A substantial proportion of the variation in Consumer Satisfaction can be explained by these two variables, suggesting that pricing strategies and the quality of service are critical drivers of customer perceptions and loyalty. For businesses, this emphasizes the importance of maintaining competitive pricing alongside consistently high service standards to enhance customer satisfaction and foster long-term engagement.